Is the existence of special schools for deaf students threatened? Selected aspects of international research in the field of surdopedagogy - Małgorzata Kupisiewicz (Studia z Teorii Wychowania)
In this article, an attempt is made to analyse selected factors influencing the current situation in the education of children with hearing impairment in Europe and worldwide. The attention is focused on exploring the importance of the impact of modern technology in providing children with hearing aids, hearing implants, undertaking early rehabilitation intervention and in the light of international education policy as a foundation for inclusive education. The key questions sought to be answered concern the dilemma of whether deaf/hard of hearing pupils need a special school or whether its existence is in jeopardy.